Technical Assistance of the Alliance of Bioversity International and International Center for Tropical Agriculture (CIAT) to the Agricultural Technologies and Innovations for Increasing the Resilience of Family Farming Production Systems in West and Central Africa project (TA-TARSPro): Achievements, lessons learnt, and way forward - Ogou, Anani; Kagabo, Desire M; Ouedraogo, Mathieu; Laderach, Peter (2024)
The Alliance of Bioversity-ClAT is providing technical support to the West and Central African Council for Agricultural Research and Development (CORAF) for the integration of Climate Smart Agriculture in the implementation of the TARSPro project in West and Central Africa, with the aim of scaling up CSA innovations, practices, and technologies in the region. This poster was produced and presented during the joint supervision mission of the donors (CORAF & Confédération Suisse). It highlights the main achievements and results obtained during the past two years; the lessons learned from the implementation of CIAT's technical assistance, and the way forward.